2015
DOI: 10.1039/c4py01774a
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization-promoted emission enhancement of poly(l-lactide) containing a fluorescent salicylideneazine center with aggregation-enhanced emission properties

Abstract: Fluorescent 1,2-bis(2,4-dihydroxybenzylidene)hydrazine (CN 4 OH) with aggregation-enhanced emission (AEE) properties was used as the initiator to induce the ring-opening polymerization (ROP) of L-lactide, resulting in polymer CN-PLLA(n)s containing an AEE-active CN center. With both pairs of p-and o-hydroxyl (OH) groups, CN 4 OH initiates an ROP of L-lactide solely with the p-OH groups and the resulting CN-PLLA(n)s are highly-emissive due to the rotational restriction imposed by the remaining p-OHs of the cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…These polymeric micelles are formed through self-assembly of amphiphilic block copolymers in aqueous solution. [133][134][135][136][137][138][139][140][141] In 2010, Jen et al reported a non-covalent method for the coencapsulation of two AIE dyes (1,1,2,3,4,5-hexaphenylsilole (HPS) and/or bis(4-(N-(1-naphthyl) phenylamino)-phenyl)fumaronitrile (NPAFN)) into three amphiphilic block copolymers (Fig. 1).…”
Section: Self-assembly Of Aie Dyes and Amphiphilic Polymersmentioning
confidence: 99%
“…These polymeric micelles are formed through self-assembly of amphiphilic block copolymers in aqueous solution. [133][134][135][136][137][138][139][140][141] In 2010, Jen et al reported a non-covalent method for the coencapsulation of two AIE dyes (1,1,2,3,4,5-hexaphenylsilole (HPS) and/or bis(4-(N-(1-naphthyl) phenylamino)-phenyl)fumaronitrile (NPAFN)) into three amphiphilic block copolymers (Fig. 1).…”
Section: Self-assembly Of Aie Dyes and Amphiphilic Polymersmentioning
confidence: 99%
“…50–55 Because of its intrinsic properties, many fluorescent molecules have been incorporated into PLLA to afford unique functionalities. 22,56–62 Hsiao et al showed that the crystallization of PLLA chains determines the AIE properties of 1,2-bis(2,4-dihydroxybenzylidene)hydrazine after incorporation into the backbone of PLLA. 57 Zhao et al incorporated TPE into the PLLA chains by living chain transfer polymerization and demonstrated that these polymers exhibit unique emission properties in the aggregated states.…”
Section: Introductionmentioning
confidence: 99%
“…22,56–62 Hsiao et al showed that the crystallization of PLLA chains determines the AIE properties of 1,2-bis(2,4-dihydroxybenzylidene)hydrazine after incorporation into the backbone of PLLA. 57 Zhao et al incorporated TPE into the PLLA chains by living chain transfer polymerization and demonstrated that these polymers exhibit unique emission properties in the aggregated states. 22 They have demonstrated that star-shaped PLLA (SSPLLA) was non-luminescent in good solvents like tetrahydrofuran (THF) and emits strongly when a poor solvent (water) was added due to aggregate formation.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of chromophores into the insulating thermoplastic polymer by the chemical method can be categorized into the following groups: chromophores as part of the backbone of polymer chains, polymer chains end-capped with chromophores, , and chromophores as core molecules in the star-shaped polymer. The major advantage of these methods is the easy fabrication of thin solid films and devices by spin-casting or inkjet printing under mild conditions. Recently, a few saturated polymers containing chromophores are prepared and tested for their photophysical properties. ,, Besides these achievements, the use of biodegradable and biocompatible polymers attracted the scientific and industrial interest because these materials can find applications as the bioprobes of real-time imaging.…”
Section: Introductionmentioning
confidence: 99%